Fascial manipulation as an adjunct to physiotherapy management in obstetric brachial plexus palsy: A case report. (July 2022) - Turazza, Costantino; Biassoni, Chiara; Day, Julie Ann; Leone, Amanda; Pirri, Carmelo; Frasca, Giovanna; Stecco, Carla
Abstract: The integrity of connective tissue sheaths surrounding the nerves influences both the severity and the potential for recovery of brachial plexus lesions. This study presents an innovative, early onset, multidisciplinary approach to obstetric brachial plexus palsy. This approach is aimed at functional recovery of the nerve lesion and includes mobilization of the fascia using the Fascial Manipulation® method. This case study discusses how, in addition to conventional treatment, interventions aimed at the fascial system can potentially affect tension around the neural sheaths, enhance proprioceptive input and facilitate movement to influence obstetric brachial plexus palsy outcomes.